PEOPLE WITH IBD WANT TO TALK ABOUT SLEEP: RECOMMENDATIONS ON WHAT TO ASK AND HOW TO RESPOND TO SLEEP COMPLAINTS. (22nd January 2022) - Salwen-Deremer, Jessica; Jagielski, Christina; Smith, Michael; Siegel, Corey
Abstract: BACKGROUND: Poor sleep occurs in 75% of people with IBD and is prospectively associated with increased risk for disease flare, hospitalization, surgery, and reduced quality of life. While IBD providers know the link between poor sleep and IBD, few are adequately armed to ask patients about sleep and provide concise, evidence based suggestions for management. We aimed to understand patients' beliefs about sleep and IBD, their treatment preferences, and offer recommendations to providers on how best to ask about and address sleep problems in this population. METHOD: We conducted an anonymous, online survey of 312 adults with Crohn's disease or ulcerative colitis who sought treatment at the Dartmouth-Hitchcock IBD center. Participants were asked about sleep patterns, thoughts and behaviors related to sleep, and open-ended questions about sleep and IBD. RESULTS: Participants ranged from 18-85 years old (M=48.6, SD=16.1) and were 66% women, 96% White. 61% of participants had Crohn's and 39% had UC; mean symptom duration=20.7 years (SD=13.7). Overall, 81% of participants endorsed some interaction between sleep and IBD. Based on thematic analysis, participants thought that their sleep was worse during flares and sleeping poorly made IBD symptoms worse, while good sleep was protective. Pain, nighttime bowel movements, and general and IBD-specific anxiety all worsened sleep. Participants with poor sleep evidenced more dysfunctional beliefs about sleep ( d =1.68, p <.001). They also were more likely to engage in behaviors that can worsen sleep, including taking daytime naps ( d =1.16, p =.03), lying in bed while in pain during the day ( d =1.19, p <.001), and worrying/planning in bed ( d =.99, p <.001). 70% of participants thought that IBD providers should ask about sleep during visits and 67% of those with poor sleep thought IBD providers should provide sleep recommendations. 83% of people with poor sleep were interested in sleep treatment and/or information, provided it was not time intensive. Access to treatment, availability, cost, lack of knowledge about treatment options, and disinterest in medication were all major barriers to seeking treatment. CONCLUSIONS: People with IBD believe there is a link between sleep and IBD and may be engaging in thought and behavior patterns that worsen sleep, and, likely, their IBD. While access to behavioral sleep medicine specialists can be limited, patients are quite receptive to getting sleep information from their IBD providers. To address these patient needs, providers may ask about weekday/weekend sleep differences and what patients do in bed besides sleep. Patients should be encouraged to maintain consistent sleep/wake times, not take naps (or nap for 20-30 minutes before lunch), use their beds only for sleep and sex, and not spend time in bed when they are not sleeping (e.g., if resting when fatigued or in pain).